N
namtuocvva18
Tính giói han:
[TEX]\lim_{x\to0}{\frac{(1+2009x)^{2010}-(1+2010x)^{2009}}{x^2}[/TEX].
.
Ta có:
[TEX](1+2009x)^{2010}=C^0_{2010}+2009C^1_{2010}x+2009^2C^2_{2010}x^2+......+2009^{2010}C^{2010}_{2010}x^{2010}[/TEX]
[TEX](1+2010x)^{2009}=C^0_{2009}+2010C^1_{2009}x+2010^2C^2_{2009}x^2+.......+2010^{2009}C^{2009}_{2009}x^{2009}[/TEX]
Lay (1)-(2) ta được:
[TEX](1+2009x)^{2010}-(1+2010x)^{2009}=(2009^2C^2_{2010}-{2010}^2C^2_{2009})x^2+x^3(.......)[/TEX]
Từ đó:
[TEX] \lim_{x\to0}{\frac{(1+2009x)^{2010}-(1+2010x)^{2009}}{x^2}=(2009^2C^2_{2010}-2010^2C^2_{2009})=\frac{2010.2009}{2} [/TEX].
Last edited by a moderator: